UKRAINIAN ENTERPRISES OF THE FOREST AND WOODWORKING INDUSTRIES’ MANAGEMENT INNOVATIONS BY THE VECTOR OF STABLE DEVELOPMENT - KULINICH, TETIANA; HYCHKA, VLADYSLAV-OLEKSII (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article reveals the problem of ensuring stable development and increasing the competitiveness of domestic enterprises in the forestry and woodworking industry, based on the observance of the concept of social responsibility of business and the use of diverse innovations. The level of profitability, development rates, innovativeness of various segments of the domestic forestry and woodworking industry in dynamics for 2014-2021 were studied. There is highlighted the list of the main production and technological, innovative, financial and economic problems that accompany the activities of enterprises in the industry, taking into account the basic directions of their development. The foreign experience of enterprises - innovators in this field of activity is analyzed. Possibilities of application of technological and organizational innovations for domestic enterprises are estimated, if the main idea of development is recognized as a socially responsible choice. The logical chain links between the goals and opportunities for the development of forestry and woodworking industry and forestry of the country are analyzed, if the key is economical, conservative and responsible attitude to forest resources, which determines the socio-ecological needs of humanity. Variants of innovative strategic decisions in the development of forestry and woodworking enterprises taking into account these needs are considered. The factors that contribute to and inhibit the implementation of innovative activities of enterprises in these industries, provided the choice of the vector of sustainable development. The article considers a set of proposals for changes that it is desirable to implement at the enterprises of the forestry and woodworking industries when they follow the vector of stable development. The proposed innovative solutions are grouped depending on the stages of wood processing and of the finished product release. Particular attention is paid to reducing the cost intensity of production, increasing resource saving and energy efficiency. In addition, complex options for overcoming the financial, economic and organizational problems of enterprises activities in the forestry and woodworking industries are outlined.